Baird-Pattinson Aetiological Classification and Phases of Delay Contributing to Stillbirths in a Nigerian Tertiary Hospital - Jacob Olumuyiwa Awoleke; Abiodun Idowu Adanikin (Journal of Pregnancy)
Purpose. This study aims to identify triggers of stillbirth in the study setting and to make suggestions to reduce the prevalence. Method. A three-year retrospective case-control study of stillbirths at Ekiti State University Teaching Hospital. Results. The stillbirth rate was 33 per 1000 births. Based on Baird-Pattinson classification of the primary obstetric causes of stillbirth, adverse intrapartum events, hypertensive diseases, and unexplained intrapartum fetal deaths were topmost causes of stillbirths. In comparison with the controls, other identified predictors of SB were grand multiparity (p=0.016), delays in seeking medical care and/or in receiving treatment (p=0.001), wrong initial diagnosis (p=0.001), inadequate intrapartum monitoring (p=0.001), and inappropriate clinical management (p=0.001). Conclusion. Stillbirth rate remains high in our setting. Elimination of obstacles to accessing care, effective management of hypertensive disorders in pregnancy, updated health facilities, improved dedication to duty, and retraining of health workers will reduce the prevalence.